The analysis on correlation of urban temperatures and the urban green spaces using GIS approach - Yahya, Nurul Hidayah; Hj. Mohd. Noor, Norzailawati (2012)

(untitled)
In recent years, rapid urbanization has transformed the spatial pattern of urban land uses worldwide that has resulted in the losses of urban green spaces apart from continuously altering the urban ecosystems. Along with it, the rising of temperatures in urban areas or what is commonly known as the “urban heat island effect” has become one of the most serious urban problems. This is especially so due to its impacts on the urban microclimate, air quality, and public health. Nowadays, the analysis of the satellite images using geographical information system (GIS) are often used to determine the impact of the land coverage (including urban green spaces) that has resulted to the changes on the surface temperature. The aim of this research is to study the correlation between the urban temperature and the urban green spaces. This research presents the findings and analysis done by previous researches. Due to the analysis that has been done, we can expect to find that the temperature may vary according to the urban hierarchy. This may due to the level of development and built-up area of the various urban centres, and the steps that has been taken by the various local authorities to address the urban heat effect. At the end of the study, we should have some insight on whether planning of the urban areas had played an important role on the outcome of the surface temperature of the particular urban areas.